MODERN METHODS OF EXTRACTING NUCLEIC ACIDS FROM BIOLOGICAL OBJECTS (Multidisciplinary Journal of Science and Technology, 2024)
The study of nucleic acids began many years ago, and each scientist used unique methods in the study. To study nucleic acids, it is necessary to isolate them first. For this reason, several DNA or RNA isolation methods have been created, each of which has its own advantages. This article teaches the most convenient, easiest, most effective methods of extracting nucleic acids.